Schizophrenia of Main Character in The Novel Words on Bathroom Walls by Julia Walton - Millen Rahmanisa Utami; Firidiansyah Firidiansyah; chandri febri santi (English Language, Linguistics, Literature, And Education Journal, 2023)
This study discusses Schizophrenia of the Main Character In The Novel Words On Bathroom Walls by Julia Walton. The researcher chose this title to provide further information to readers and especially in the English literature department about Schizophrenia. The purpose of this study is to find and explain the first, the types of schizophrenia that exist in the main character Adam Petrazelli, the second the symptoms of schizophrenia, and the third way of treating schizophrenia. Researchers used three theories. The first theory is about the types of schizophrenia presented by the American Psychiatric Association, the second theory is conveyed by Keliat which explains the symptoms of schizophrenia, and the third theory by Ross Willson explains the treatment of Schizophrenia. This type of research uses descriptive qualitative research. sources of data in this study were all conversations spoken by all characters in the novel "Words On Bathroom Walls By Julia Walton" containing sentences related to schizophrenia. The data collection technique used was documentation. The results of this research indicate that: from the types of schizophrenia there is one that has been found, namely Paranoid Type which has been analyzed, the researcher only managed to find one symptoms namely positive symptoms and in these positive symptoms there are two characteristics found by the researcher (Hallucination and Behavior Change), there are two ways to cure schizophrenia Medical Intervention and Psychosocial Intervention.